2019
DOI: 10.1016/j.neuroscience.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial representations in the superior colliculus are modulated by competition among targets

Abstract: Selecting and moving to spatial targets are critical components of goal-directed behavior, yet their neural bases are not well understood. The superior colliculus (SC) is thought to contain a topographic map of contralateral space in which the activity of specific neuronal populations corresponds to particular spatial locations. However, these spatial representations are modulated by several decision-related variables, suggesting that they reflect information beyond simply the location of an upcoming movement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 90 publications
2
22
0
Order By: Relevance
“…neurons: 49/72; Ipsi. neurons = 23/72; p = 0.0022, Χ 2 test), consistent with previous results [11][12][13] . Within the population of GABAergic neurons, we also found that more neurons preferred the contralateral than the ipsilateral choice ( Fig.…”
Section: Endogenous Gabaergic Sc Activity Corresponds To Contralaterasupporting
confidence: 92%
See 4 more Smart Citations
“…neurons: 49/72; Ipsi. neurons = 23/72; p = 0.0022, Χ 2 test), consistent with previous results [11][12][13] . Within the population of GABAergic neurons, we also found that more neurons preferred the contralateral than the ipsilateral choice ( Fig.…”
Section: Endogenous Gabaergic Sc Activity Corresponds To Contralaterasupporting
confidence: 92%
“…When the sensory evidence for the rewarded choice is strong (i.e., on easy trials), input from upstream regions may dominate processing in the SC (or outweigh SC contributions at downstream circuits in the brainstem). Conversely, when the sensory evidence is weak (i.e., on difficult trials), intrinsic SC processing, including via the GABAergic SC neurons studied here, may have more weight in determining the output of competing choices and therefore exert a stronger influence over spatial choice 13 .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations